Arab-Palestinian society in the Israeli political system integration versus segregation in the twenty-first century - Zeedan, Rami (Lexington Books, 2019)
The book examines the integration of Arab-Palestinian society, an ethnic minority within the nation-state of Israel, in Israel's political system and the relation between political trends, leadership, and identity. It also delves into the causes of the crisis in Arab localities and the relations to the local political structure.